Critical import insurance as a tool to support entrepreneurs under sanctions - А. V. Averin; A. F. Baranova; A. M. Kutyrev (Вестник университета)
The article substantiates the relevance of state support for critical imports in modern conditions of political and economic restrictions. The current economic and political conditions of Russia’s development introduce significant business risks when concluding import contracts for importing critical goods and implementing additional supportive measures for importers of those goods that are duly recognized as critically important for the country’s economic development. As a result of the conducted research the conclusion about the lack of theoretical approaches to the understanding of critical imports and normative fixation of the sought concept has been made. Based on the analysis of regulatory legal acts of the Eurasian Economic Union and federal legislation of Russia, the system of support for critical imports at the supranational level and the level of the Russian Federation has been described. The commodity structure of the critical imported products lists has been analyzed. On the basis of them the conclusion about the large-scale dependence of the Russian Federation on foreign-made goods has been made. The necessity of state support of insurance of advance payments for imports of critical goods has been assessed and the algorithm of state support of advance payments insurance for critical goods imports described. The conclusion about the need for a comprehensive approach to support critical imports has been formulated and the one of the possible tools for its implementation proposed.